Evaluating cloves as a potential substitute for antimicrobials in nursery pig diets - R G Main; J Ernest Minton; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2001)
We conducted two trials to evaluate the effects of feeding graded levels of cloves to weanling pigs as a substitute for antimicrobials. In the first trial, improvements in ADG were observed in pigs fed the lowest level of clove addition (0.5%) and for those fed carbadox (50 g/ton). The higher levels of clove inclusion (1.0% and 2.0%) tended to reduce feed intake. A second trial was conducted evaluating performance of pigs fed diets containing 0.125%, 0.25% and 0.5% cloves (a different batch than used in trial 1). The was no ADG improvement from added cloves as was observed in the first trial, and the higher clove concentrations tended to reduce feed intake. The inconsistent response to added cloves between our two studies merits further investigation.; Swine Day, Manhattan, KS, November 15, 2001
Keywords: Swine day; 2001; Kansas Agricultural Experiment Station contribution; no. 02-132-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 880; Swine; Clove; Spice; Antimicrobials